Colletive land, commune land: reality or mystification? - Maria de Fátima Ferreira Rodrigues (GEOUSP: Espaço e Tempo, 1998)
This paper is about a research realized in a peasant social group that lives in the Maceió Settlem ent municipality of Itapipoca (Ceará north Seaside) and is also about its social reproductions strategies, chiefly, its social practices that originated the com m unitarian-work